Le porte lignee di Santa Sabina all’Aventino: tra liturgia stazionaria e funzione iniziatica (Il nartece di Santa Sabina, II) - Foletti, Ivan (Hortus Artium Medievalium, 2014)
Abstract This essay is dedicated to the function of the narthex of the basilica of Santa Sabina in Rome. Starting from a reflection on the “liminal zone”, the use of the atrium or the narthex in the culture and tradition of Late Antiquity will be defined. In this way, the atrium is shown to be a place designed to accommodate the catechumens and penitents. In second place, the manner in which this definition can be applied to the narthex of Santa Sabina will be analyzed. Liturgical sources, epigraphy, but also archaeological data confirm that the Aventine’s narthex was primarily dedicated to the catechumenate and initiatory rites. The wooden door, the only figurative component of the original space, which seems to emphasize precisely an initiatory function, also supports this conclusion.